Financial literacy among SME’s in Malaysia - Thabet, Omer; Abd Manaf, Atiqah; Ali, Fazlin; Kantakji, Mazhar (Maya Global Education Society, 2019)
Recently, financial literacy received considerable attention on not only business level but individual and government levels. This is because the financial illiteracy will lead to individual and business failure especially with incessant incidents of global financial crisis that imply the risk that people and business across the world facing. Financial Literacy enables individuals and business to comprehend the use and purposes of money and take wise financial decisions According to Van Rooij et al. (2011) literacy is one of the major determinants of the success or failure of the business. Similarly, Greenspan (2002) suggested that the financial literacy will help an individual know more how to manage their personal financial, financial planning and know how to make strategic investment decisions for their long-term savings. For small and medium enterprises (SME’s), the failure rate is too high in their first five years in many different countries. For instance, In United State (US), a new business had a 48.4 % chance of surviving five years (Business Employment Dynamics, Bureau of Labor Statistics, 2013). Similarly, in Australia the SMEs reported failure rate of 23% (Watson, 2003). The main reason for this failure is the lack of these SME’s financial literacy (OECD, 2013). In Malaysia, according to the Department of Statistic Malaysia (2017), the total number of SMEs establish in Malaysia were 907,065 units in 2016 with 37.1% contribution to Malaysian GDP and providing 66% of total employment in the country. However, Ming-Yen et al. (2013) stated that the failure rate among Malaysian SME’s was increased lately. Therefore, this paper tries to address the current level of the main reasons caused this failure found in the literature (financial literacy) among SMEs in Malaysia.